DEVELOPMENT OF ENERGY-SAVING COMPETENCIES AMONG CONSUMERS - Karov Batir Khamro ogli (American Journals, 2023)
In this article, raising the quality of education to a new level is based on the role of modern approaches in the development of basic competencies of students in the field of science. The importance of an integrative approach in the development of basic competencies is emphasized.
Keywords: Competence, integration, communication, technology, e-learning, knowledge, skill, competency, ability, efficiency, flexibility, achievement, success, understanding, “efficiency, learning, haiku, characteristic, quality, quantity.